A Design Study of Dual-Stator Permanent Magnet Brushless DC Motor - Wang Yaling; Xu Yanliang Xu Yanliang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Dual-stator permanent magnet brushless DC Motor (DSBLDC) features high efficiency and torque-density. As DSBLDC could operate in various states according to different winding connection modes, it is fully qualified for electric vehicle (EV) drive. Unfortunately, due to the particular dual-stator structure, this kind of motor is difficult to be designed by available design methods. However, this paper demonstrates that a DSBLDC with series magnetic circuit structure can be regarded as being consisted of two independent BLDCs, an inner-rotor BLDC and an outer-rotor BLDC. Thus, the DSBLDC can be divided into two single-stator BLDCs. Based on this demonstration, the design method is verified by finite element analysis (FEA), and the basic design steps are given. Furthermore, experimental results of the prototype motor have verified the correction of the method, which also indicates that the motor with superior performance is adapted to EV drive.